EFFORTS TO IMPROVE THE OUTCOMES OF LEARNING IN ISLAMIC RELIGIOUS EDUCATION ON THE MATERIAL OF THE LETTER AN-NASR THROUGH THE APPLICATION OF THE DISCUSSION METHOD - Kasturi (Program Studi Pendidikan Profesi Guru Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry Banda Aceh, 2025)
Islamic Religious Education is a process of guidance by students towards the development of the soul and body. The weakness of the learning process developed by teachers is one of the problems faced by the world of education. The task of Islamic religious teachers is to guide, teach and train students. Teachers tend to deliver lesson materials through lectures, group learning, but only a few students are classified as active, so it is necessary to improve learning outcomes. One effort that can be done is to apply a learning method that aims to improve student learning outcomes and student motivation. This research method uses Classroom Action Research (CAR) which consists of 2 cycles. Based on the results of the study, there was an increase in learning achievement and maximum KKM values ​​and was proven by the average value in cycle I of 63% while in cycle II there was a higher increase of 77%.